2020
DOI: 10.1140/epjc/s10052-019-7604-8
|View full text |Cite
|
Sign up to set email alerts
|

BCJ numerators from differential operator of multidimensional residue

Abstract: In previous works, we devised a differential operator for evaluating typical integrals appearing in the Cachazo-He-Yuan (CHY) forms and in this paper we further streamline this method. We observe that at tree level, the number of free parameters controlling the differential operator depends solely on the number of external lines, after solving the constraints arising from the scattering equations. This allows us to construct a reduction matrix that relates the parameters of a higher-order differential operator… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 50 publications
0
12
0
Order By: Relevance
“…The reduced Pfaffian has been studied quite extensively in the literature [32][33][34][35][36][37][38][39][40][41]. The expression given by the reduced Pfaffian is not very well suited to generalise towards off-shell momenta, unphysical polarisation or away from the solutions of the scattering equations.…”
Section: The Polarisation Scattering Formmentioning
confidence: 99%
“…The reduced Pfaffian has been studied quite extensively in the literature [32][33][34][35][36][37][38][39][40][41]. The expression given by the reduced Pfaffian is not very well suited to generalise towards off-shell momenta, unphysical polarisation or away from the solutions of the scattering equations.…”
Section: The Polarisation Scattering Formmentioning
confidence: 99%
“…It is curious to note that the objects that the kinematic Lie algebra should compute, the kinematic BCJ numerators, are under better control than the algebra itself. Numerators that manifest the color-kinematics duality have been constructed at any multiplicity for tree-level amplitudes in pure Yang-Mills theory [20][21][22][23][24][25][26][27]. For supersymmetric Yang-Mills theory, it has been observed that a recursive construction similar to Berends-Giele recursion [28] can be used to generate BCJ numerators after using appropriate non-linear gauge transformations [23].…”
Section: Introductionmentioning
confidence: 99%
“…The duality provides a rich structure to tree-level amplitudes [20,24,[35][36][37][38][39][40][41][42][43][44][45][46], most notably through the color-ordered n-point gluon amplitudes, which are constrained by the so-called BCJ relations [13,47,48] -these can be used to eliminate all but (n − 3)! independent amplitudes.…”
Section: Introductionmentioning
confidence: 99%